Efficacy Evaluation of Civil-Works Mud as Soil Matrix Modified by Organic Amendments - Yuan Su; Qian Zhang; Junwei Tang; Juanjuan Yin; Kai Zhong; Jingying Gu; Zicong Xiong; Haile Wu; Xingzhi Pang; Chaolan Zhang (Agriculture)
Converting civil-works mud (CWM) into soil matrix is a significant method for resource utilization, effectively mitigating CWM accumulation. In this study, CWM was utilized as a soil matrix and modified with three organic materials: pig manure, biochar, and corn straw. Field experiments were conducted using pig manure (PM), pig manure combined with biochar (PMB), and pig manure combined with straw (PMC), with the total organic matter content of the amendments applied in each treatment maintained at a consistent level. The physicochemical properties and soil matrix microbial biomass for all treatments were determined at the time of corn harvest. Additionally, the soil quality index (SQI) was calculated to evaluate the effectiveness of the various treatments. The results indicated that the addition of organic amendments significantly enhanced the physicochemical and soil microbial properties of soil matrix, significantly increasing the crop yield. Among the treatments, the application of pig manure combined with biochar (PMB) significantly improved the quality of soil matrix, with the SQI increasing by 65.2 times compared to soil matrix. This treatment achieved a crop yield of 5525 kg/ha, and the safety of the crops in all treatments complied with the National Food Safety Standard Limits of Contaminants in Foods. This study proposes a novel and feasible approach for the resource utilization of CWM, and the improved soil matrix can help alleviate the increasing issue of soil resource scarcity.